Thrombophilia gene mutations in relation to recurrent miscarriage - Abdelsalam, Tawfik; Karkour, Tarek; Elbordiny, Magdy; Shalaby, Dina; Abouzeid, Ziad S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Recurrent pregnancy loss is multifactorial involving clinical and biological risk factors. Evidence addressed the association of inherited thrombophilia with recurrent pregnancy loss and other serious pregnancy complications. However, the relation between thrombophilia associated gene mutations and adverse obstetric outcome is controversial and data in the literature are inconsistent. The aim of this study was to investigate the prevalence of thrombophilia associated gene mutations (factor V Leiden, prothrombin gene G20210A and methylene-tetrahydrofolate reductase MTHFR C677T) in relation to recurrent miscarriage. Methods: Case control study conducted on 200 women recruited from Elshatby Maternity Hospital clinics. The cases group included 100 women with history of three or more unexplained consecutive pregnancy losses, while 100 healthy age matched women with no history of recurrent miscarriages served as controls. Blood samples were collected from all women enrolled in the study for DNA extraction and genotype analysis. Factor V, prothrombin and MTHFR gene mutations were assayed based on polymerase chain reaction (PCR) and reverse-hybridization. Results: The prevalence of Factor V Leiden and prothrombin gene G20210A mutations did not differ significantly between cases and controls. However, MTHFR C667T mutations and the total prevalence of the three gene mutations were significantly increased in the patients group compared to controls (p=0.001, p=0.003 respectively). The prevalence of combined thrombophilia of Factor V Leiden and MTHFR C677T was significantly increased in the patients group compared to controls (p=0.032). Regarding homozygosity of each of the gene mutations, no homozygosity was detected in controls and heterozygotes were significantly increased in the patients group compared to homozygotes. Conclusions: MTHFR mutations and the total prevalence of the three gene mutations were significantly increased in the patients group compared to controls. There was a significant increase in the prevalence of combined thrombophilia (Factor V Leiden and MTHFR C677T) in the patients group compared to controls without involvement of prothrombin gene.